2008
DOI: 10.1016/j.jcrs.2007.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Blade source effect on laser in situ keratomileusis flap thickness with the Amadeus I microkeratome

Abstract: PURPOSE-To determine the effect of different blades on laser in situ keratomileusis (LASIK) flap thickness created with the Amadeus I microkeratome (Ziemer Ophthalmic Systems). SETTING:METHODS-This retrospective nonrandomized comparative case study from January 2005 through June 2006 compared LASIK flap thickness created with blades from 2 manufacturers: the Surepass from Surgical Instrument Systems and distributed by AMO and the ML7090 CLB distributed by Med-Logics, Inc. Sex, preoperative corneal thickness, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Based on previous studies from our group regarding this microkeratome and blade combination, 16, 17 we anticipated the flap thickness to be 107 ± 12 µm, which is essentially identical to the results presented herein, and our reported range of central thicknesses (60 microns as measured with ultrasound pachymetry, 40 microns as measured with OCT) falls well within the reported ranges for femtosecond flaps.…”
Section: Discussionsupporting
confidence: 89%
“…Based on previous studies from our group regarding this microkeratome and blade combination, 16, 17 we anticipated the flap thickness to be 107 ± 12 µm, which is essentially identical to the results presented herein, and our reported range of central thicknesses (60 microns as measured with ultrasound pachymetry, 40 microns as measured with OCT) falls well within the reported ranges for femtosecond flaps.…”
Section: Discussionsupporting
confidence: 89%
“…After that date, the refractive surgery center switched to the ML7090 CLB blade (Med-Logics, Inc.) for comparative evaluation. A previous study 13 found that flaps created with the Amadeus I microkeratome were thinner and had less variance when an ML7090 CLB blade (blade A) was used than when a Surepass blade (blade B) was used.…”
Section: Methodsmentioning
confidence: 93%
“…A previous study 13 found that flap thickness with this mechanical micro-keratome varied depending on the blade used.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Although femtosecond lasers and modern microkeratomes create thinner flaps with improved predictability 10, 1822 thicker than expected flaps can still occur with any device. 22 Therefore, we recommend using average flap thickness plus 2 standard deviations for preoperative planning of residual stromal bed thickness and diligence with measuring flap thicknesses, especially in cases with potentially borderline RSB.…”
Section: Discussionmentioning
confidence: 99%